2017
DOI: 10.1525/collabra.77
|View full text |Cite
|
Sign up to set email alerts
|

Cash or Credit? Compensation in Psychology Studies: Motivation Matters

Abstract: It is common practice for psychology researchers to recruit their sample of participants from the undergraduate student population. Participants are typically compensated with partial course credit or a monetary payment. The current study reveals that the motivation to participate in a study (cash versus course credit) can relate to performance on a behavioral task of rewarded memory. In Experiment 1, undergraduate participants were recruited and compensated for their time with either partial course credit or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
0
15
0
2
Order By: Relevance
“…To avoid an increase in performance motivation, subjects were only able to receive either a predetermined amount of course credit or monetary compensation. This decision was based on research findings which concluded that performance-based compensations are suspected to cause an increase in performance motivation (Bowen & Kensinger, 2017; Brase, 2009). No such significant influence on performance motivation was found for flat-fee monetary compensation and course credit (Brase, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…To avoid an increase in performance motivation, subjects were only able to receive either a predetermined amount of course credit or monetary compensation. This decision was based on research findings which concluded that performance-based compensations are suspected to cause an increase in performance motivation (Bowen & Kensinger, 2017; Brase, 2009). No such significant influence on performance motivation was found for flat-fee monetary compensation and course credit (Brase, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…(Landry, Gagné, Forest, Guerrero, Séguin & Papachristopoulos, 2017) Apabila upah dan kesejahteraan karyawan diabaikan oleh perusahaan maka akan menimbulkan berbagai masalah bagi perusahaan, membuat para karyawan malas bekerja, melakukan pemogokan-pemogokan, atau mungkin melakukan usaha-usaha untuk pindah ke perusahaan lain yang lebih menjamin kesejahteraan mereka. (Bowen & Kensinger, 2017) Tetapi sebaliknya, apabila perusahaan memberikan upah dan kesejahteraan yang sesuai dengan kinerja karyawan, maka hal ini merupakan salah satu factor dapat memotivasi mereka untuk dapat meningkatkan produktifitas kerja karyawan.…”
Section: Pendahuluanunclassified
“…Hasil penelitian tersebut dinyatakan sesuai setelah dibandingkan dengan pendapat Bowen & Kensinger (2017) yang mengemukakan bahawa salah satu cara manajemen untuk meningkatkan prestasi kerja, memoyivasi dan meningkatkan kepuasan dan kinerja karyawan adalah melalui kompensasi.…”
Section: Hasil Dan Pembahasanunclassified
“…In contrast, behaviors associated with unpleasant consequences will be engaged in less frequently. This notion has been a cornerstone of theorizing on the mechanisms of motor learning specifically [ 15 , p. 113] and is in general apparent in the common practice of using incentives to guide behavior or improve performance (e.g., verbal encouragement to boost student engagement, [ 16 ]; monetary incentives to increase performance of study participants, [ 17 19 ]). In addition, the role of incentives in behavioral regulation has more recently been bolstered by linking variations in incentive value to systematic changes in neural correlates, [e.g., 20 22 ], especially in the context of motor performance [ 23 , p. 219].…”
Section: Introductionmentioning
confidence: 99%